The Effectiveness of the Mechanism for Attracting Household Savings in the Investment Strategy of the Ukrainian Economy - Riabtsev, Dmytro; Shevchuk, Volodymyr; Pulcha, Dmytro; Slavkova, Olena; Vakulich, Maria (International Journal of Economics and Financial Issues, 2025)
The aim of the study is to assess the impact of traditional macroeconomic factors and non-traditional factors on the effectiveness of the mechanism for attracting household savings. The study employed correlation analysis, regression analysis using the ordinary least squares (OLS), and building of a multivariate econometric model. Analysis of variance (ANOVA) was also used to test the statistical significance of variables. The data were obtained from official sources and expanded with additional indicators. The results showed that the model has high explanatory power. Traditional factors, such as inflation and the hryvnia (UAH) to US dollar exchange rate, have the greatest impact on the volume of deposits. Non-traditional factors also demonstrated significance. Attracting household savings largely depends on the combination of macroeconomic stability and the introduction of innovative financial instruments. It is recommended to develop financial literacy, digital deposit platforms, and expand state incentive programmes to increase the efficiency of the savings attraction mechanism. The obtained results provide new tools for developing economic policy. The results of the study enable integrating mechanisms for attracting household savings into the overall investment strategy of the Ukrainian economy, increasing its adaptability to modern challenges.